Therapeutic targeting of glutaminolysis as an essential strategy to combat cancer - Matés, José M.; Di Paola, Floriana J.; Campos-Sandoval, José A.; Mazurek, Sybille; Márquez, Javier; Justus Liebig University Giessen (My University, 2019)
Metabolic reprogramming in cancer targets glutamine metabolism as a key mechanism to provide energy, biosynthetic precursors and redox requirements to allow the massive proliferation of tumor cells. Glutamine is also a signaling molecule involved in essential pathways regulated by oncogenes and tumor suppressor factors. Glutaminase isoenzymes are critical proteins to control glutaminolysis, a key metabolic pathway for cell proliferation and survival that directs neoplasms’ fate. Adaptive glutamine metabolism can be altered by different metabolic therapies, including the use of specific allosteric inhibitors of glutaminase that can evoke synergistic effects for the therapy of cancer patients. We also review other clinical applications of in vivo assessment of glutaminolysis by metabolomic approaches, including diagnosis and monitoring of cancer.
Keywords: Glutaminolysis; ddc:570